2015
DOI: 10.3393/ac.2015.31.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial on the Incidence of Wound Infection and Patient Satisfaction After Stoma Closure: Comparison of Two Skin Closure Techniques

Abstract: PurposeSurgical site infection (SSI) is one of the most common complications that can occur after stoma closure. Reports have described differences in the incidence of wound infection depending on the skin closure technique, but there is no consensus on the ideal closure technique for a stoma wound. The aim of this study was to compare the incidence of SSI and the patient satisfaction between a circumferential purse-string approximation (CPA) and a primary linear closure (PC) of a stoma wound.MethodsThis prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…The purse-string closure method has been criticized because of the time required for wound healing. However, the wound healing time following purse-string closure has been reported to be shorter than that following primary closure [ 5 , 7 ], which is the same as the results reported by the authors of "Clinical trial on the incidence of wound infection and patient satisfaction after stoma closure: Comparison of two skin closure techniques" [ 9 ]. The way in which an open wound affects the quality of life of a patient needs to be investigated further because a higher infection rates is also associated with patient dissatisfaction.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…The purse-string closure method has been criticized because of the time required for wound healing. However, the wound healing time following purse-string closure has been reported to be shorter than that following primary closure [ 5 , 7 ], which is the same as the results reported by the authors of "Clinical trial on the incidence of wound infection and patient satisfaction after stoma closure: Comparison of two skin closure techniques" [ 9 ]. The way in which an open wound affects the quality of life of a patient needs to be investigated further because a higher infection rates is also associated with patient dissatisfaction.…”
supporting
confidence: 67%
“…The authors of "Clinical trial on the incidence of wound infection and patient satisfaction after stoma closure: Comparison of two skin closure techniques" comparing purse-string with primary closure for ileostomy wounds demonstrated a lower incidence of SSI and a higher patient satisfaction when ileostomy wounds were closed using the purse-string method [ 9 ]. Although the study was a retrospective one, the patient populations in the two arms of the trial were well matched in most respects such as indications, types of stoma, and times to stoma closure.…”
mentioning
confidence: 99%
“…This study, however, revealed longer time to complete healing with the purse-string technique (32 vs. 19 days; p < 0.0001) when compared with primary closure. 42 Data have repeatedly suggested that purse-string closure of the stoma closure site results in lower surgical site infections and improved patient satisfaction when compared with primary closure. 35,36,[41][42][43][44][45] Hartmann's Reversal…”
Section: Wound Managementmentioning
confidence: 99%
“…Purse-string suturing has one of the lowest infection rates, and its usefulness has been demonstrated [ 1 , 4 , 11 ]. However, this method can take up to 30 days for granulation and epithelialization [ 13 ]. Continuous wound care and outpatient visits are required until the wound is healed, and it may be difficult for elderly patients to perform self-care procedures such as cleaning the wound.…”
Section: Discussionmentioning
confidence: 99%